At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Alright, let's work through the problem step-by-step:
We are given the equation:
[tex]\[ y = \frac{4r - 7}{h} \][/tex]
Our goal is to express [tex]\( r \)[/tex] in terms of [tex]\( h \)[/tex] and [tex]\( y \)[/tex].
Step 1: Start by eliminating the denominator [tex]\( h \)[/tex] from the right-hand side. To do this, multiply both sides of the equation by [tex]\( h \)[/tex]:
[tex]\[ y \cdot h = 4r - 7 \][/tex]
Step 2: Next, isolate the term involving [tex]\( r \)[/tex] on one side of the equation. To do this, add 7 to both sides of the equation:
[tex]\[ y \cdot h + 7 = 4r \][/tex]
Step 3: Finally, solve for [tex]\( r \)[/tex] by dividing both sides of the equation by 4:
[tex]\[ r = \frac{y \cdot h + 7}{4} \][/tex]
Thus, the expression for [tex]\( r \)[/tex] in terms of [tex]\( h \)[/tex] and [tex]\( y \)[/tex] is:
[tex]\[ r = \frac{y \cdot h + 7}{4} \][/tex]
Given specific values [tex]\( h = 2 \)[/tex] and [tex]\( y = 3 \)[/tex], we can substitute these values into our equation:
[tex]\[ r = \frac{3 \cdot 2 + 7}{4} \][/tex]
[tex]\[ r = \frac{6 + 7}{4} \][/tex]
[tex]\[ r = \frac{13}{4} \][/tex]
[tex]\[ r = 3.25 \][/tex]
Therefore, the value of [tex]\( r \)[/tex] is [tex]\( 3.25 \)[/tex].
We are given the equation:
[tex]\[ y = \frac{4r - 7}{h} \][/tex]
Our goal is to express [tex]\( r \)[/tex] in terms of [tex]\( h \)[/tex] and [tex]\( y \)[/tex].
Step 1: Start by eliminating the denominator [tex]\( h \)[/tex] from the right-hand side. To do this, multiply both sides of the equation by [tex]\( h \)[/tex]:
[tex]\[ y \cdot h = 4r - 7 \][/tex]
Step 2: Next, isolate the term involving [tex]\( r \)[/tex] on one side of the equation. To do this, add 7 to both sides of the equation:
[tex]\[ y \cdot h + 7 = 4r \][/tex]
Step 3: Finally, solve for [tex]\( r \)[/tex] by dividing both sides of the equation by 4:
[tex]\[ r = \frac{y \cdot h + 7}{4} \][/tex]
Thus, the expression for [tex]\( r \)[/tex] in terms of [tex]\( h \)[/tex] and [tex]\( y \)[/tex] is:
[tex]\[ r = \frac{y \cdot h + 7}{4} \][/tex]
Given specific values [tex]\( h = 2 \)[/tex] and [tex]\( y = 3 \)[/tex], we can substitute these values into our equation:
[tex]\[ r = \frac{3 \cdot 2 + 7}{4} \][/tex]
[tex]\[ r = \frac{6 + 7}{4} \][/tex]
[tex]\[ r = \frac{13}{4} \][/tex]
[tex]\[ r = 3.25 \][/tex]
Therefore, the value of [tex]\( r \)[/tex] is [tex]\( 3.25 \)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.